KARYA MUSIK YOUTH KELOMPOK MUSIK SOLOENSIS (Kajian Proses Penciptaan Dan Makna Teks Lagu) - Bekti Setyo Utomo (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
ABSTRACT This paper focuses on the creative process of the song entitled Youth, and also the meaning of the lyrics. The lyrics and the structure of the music presented is a contradiction between the lyrics and the musical form. The song Youth created by the Soloensis music group used the major scales. Then, the character of their musical composition is cheerful and uses instruments that are not normally played in their works. The song Youth is a song with a message about the anxiety of the creator's youth. In the end, the content of the message is transformed into a song with a contrasting musical composition. This music constructs an atmosphere of anxiety and sadness using the diatonic major scale which is usually cheerful. Kata kunci : musik youth, soloensis, makna teks lagu